Evolutionary and mutational characterization of the first H5N8 subtype influenza a virus in humans - Ding, Lin; Li, Jie; Li, Xue; Qu, Bingqian (Pathogens, 2022)
Highly pathogenic influenza A virus H5 subtype remains a risk for transmission in humans. The H5N8 subtype has caused multiple outbreaks in poultry in Europe over the past few winters. During one recent outbreak in poultry in Astrakhan, workers on the farm were also infected. So far, little is known about how this virus evolves and adapts to infect humans. Here, we performed a time-resolved phylogenetic analysis of 129 HA sequences representing all 1891 available H5N8 viruses collected from 2010 to 2020. We also conducted a whole-genome scan on the human virus at the protein level. We found that H5N8 viruses have spilled over in 34 European countries during the flu season of 2020-2021. These viruses underwent two significant evolutionary steps during 2015-2016 and after 2018. Furthermore, we characterized a number of critical mutations in all viral proteins except PB1-F2, which contribute to increased virulence and avian-to-human adaptation. Our findings suggested that the accumulated mutations under evolution led to quantitative and qualitative changes, likely allowing the virus to spread to humans. Given that the H5N8 virus is co-circulating with other H5 viruses in Europe, the risk of a pandemic should not be underestimated. Continental surveillance and pandemic preparedness are to be established.
Gesehen am 24.08.2022
This article belongs to the special issue "Emerging respiratory tract infections"